Relationship between information overload, communication overload, social interaction, invasion of privacy and employee engagement in Malaysian banking industry - Dayangku Siti Zulaiha, Awang Marbawi (2024)
For the past few decades numerous studies have attempted to explore the relative importance of understanding employee engagement. Realizing the need to sustain in the banking industry, this study was conducted to explore the factors influencing employee engagement. Further, the study examines the relationship between information overload, communication overload, invasion of privacy, social interaction and employee engagement. By adopting the survey approach, a sample of 337 data were collected. The findings revealed significant negative relationships between employee engagement and both information and communication overload, social interaction as well as invasion of privacy. The discussion of the research found that emphasizing the need for balanced information flow, clear communication protocols, privacy-preserving measures, and fostering interpersonal connections is crucial. The impact of the study shows and provides theoretical insights and practical recommendations to enhance engagement and productivity in the banking sector. Based on rigorous reviewing of the literature, instrument designing, followed by subsequent pilot testing, the final analysis revealed that employee engagement can be predicted by using information overload, communication overload, and invasion of privacy within the industry.